2001
DOI: 10.1096/fj.00-0836fje
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptors are required for up‐regulation of neuronal 5‐lipoxygenase (5LOX) expression by dexamethasone

Abstract: 5-lipoxygenase (5LOX) is the key enzyme in the synthesis of leukotrienes from arachidonic acid. Hyperglucocorticoidemia, dexamethasone, and aging up-regulate 5LOX in the brain, including the cerebellum in vivo. We studied the mechanisms of dexamethasone-triggered 5LOX upregulation in primary cultures of rat cerebellar granule neurons (CGN). We measured 5LOX mRNA and protein contents, and the formation of cysteinyl leukotrienes (LTC 4 , LTD 4 , and LTE 4 7KHGH[DPHWKDVRQH0RUµM)-increased 5LOX mRNA and protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Another crosstalk between the activated forms of aryl hydrocarbon receptor and GR was also reported [42]. Here we found GR was required for ALOX5 activation, consistent with a previous work conducted in neurons [43]. We recently showed that LXA 4 analog partially alleviated Dex-induced IUGR in rats [7], further supporting FIG.…”
Section: Zhang Et Alsupporting
confidence: 91%
“…Another crosstalk between the activated forms of aryl hydrocarbon receptor and GR was also reported [42]. Here we found GR was required for ALOX5 activation, consistent with a previous work conducted in neurons [43]. We recently showed that LXA 4 analog partially alleviated Dex-induced IUGR in rats [7], further supporting FIG.…”
Section: Zhang Et Alsupporting
confidence: 91%
“…Chronic treatment with corticosterone increases message and protein of 5LO in the rat cerebellum, and blockade of the glucocorticoid receptor reduces dexamethasone-induced message and expression of 5LO in cultured primary rat cerebellar granular neurons (Uz et al, 1999; Uz et al 2001), suggesting 5LO expression is directly affected by stress hormones in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of 5-LO is susceptible to hormonal regulation, since higher levels are observed in conditions of melatonin deficiency and/or hyperglucocorticoidemia [10, 11], both of which are common in elderly subjects [12]. Although in general upregulation of 5-LO might serve a physiological purpose, during the aging process, it may also increase the vulnerability of the cardiovascular system and CNS to different insults/stressors [13].…”
Section: The 5-lo Pathway In the Vasculature And Central Nervous Smentioning
confidence: 99%